Survey on Indigenous Protozoa in Effluent Treatment Plant of a Textile Dyeing Industry - Hassan, MM; Alam, MZ; Anwar, MN (Bangladesh Journal of Microbiology, 2016)
Effluents from textile dyeing industry are so toxic that it threatens the environment in various ways. Hence, it should be treated before discharge. Biotreatment is the most promising approach for the remediation of toxic industrial effluent where microorganisms breakdown the dye molecule into its nontoxic basic elements. In effluent treatment plants (ETP), protozoa accelerate dye degradation process by stimulating the growth of acting bacteria and also play a key role in clarification of the secondary effluent through engulfment of excess bacteria. However, only a few types of protozoa can survive and thrive on this toxic environment. This study deals with the identification and survey of the protozoa present in the effluent treatment plant of a dyeing industry. Collected samples were stained with Leishman reagent and observed under microscope. A total of 10 protozoa were observed and 6 of them were identified up to genus viz. Paramecium, Nassula, Opercularium, Stylonychia, Telotrochidium, Trachelomonas on the basis of their morphological and structural arrangements observed under microscope. Hence, this study reveals that some protozoa can thrive in toxic dyeing effluent and play an important role in maintaining the sustainability of an effluent treatment plant (ETP). Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 39-42